A Literature Review of Inflammation and Its Relationship with the Oral Cavity - Luciano Silva (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2015)
Objective: This article presents a literature review which relates the processes, interactions, classification and the vascular and clinical characteristics of inflammation relating it with the oral cavity and describing the main cell types and chemical mediators used for its establishment. Materials and Methods: it was used as source of research the following databases: MEDLINE, LILACS, BBO, Cochrane Library, Scielo, PubMed and the database of CAPES. Results: much information was obtained concerning the chemical mediators as well as the main cell types responsible for the establishment of inflammation and its relationships with the oral cavity.